2010
DOI: 10.1177/0022034510364489
|View full text |Cite
|
Sign up to set email alerts
|

Building Caries Risk Assessment Models for Children

Abstract: decayed, missing, filled teeth in primary dentition (dmft); receiver operation characteristics (ROC); relative risk (RR); confidence interval (CI); National Institutes of Health (NIH); World Health Organization (WHO); US Department of Health and Human Services (US/DHHS); American Academy of Pediatric Dentistry (AAPD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
183
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(197 citation statements)
references
References 21 publications
7
183
0
7
Order By: Relevance
“…Prediction models which include a variety of factors seem to increase the accuracy of the prediction in young children (Fontana et al, 2010b). A recent study in Singapore showed that caries prediction based on a questionnaire reached a sensitivity/specificity of 0.82/0.81 in 3-to 6-year-olds (Gao et al, 2010). However, additional risk factors (e.g., plaque, bacterial tests, salivary factors, exposure to fluoride) do not seem to markedly improve the prediction in older schoolchildren, adolescents, and adults (Disney et al, 1992;Vanobbergen et al, 2001; Stenlund et al, 2002;Twetman and Fontana, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Prediction models which include a variety of factors seem to increase the accuracy of the prediction in young children (Fontana et al, 2010b). A recent study in Singapore showed that caries prediction based on a questionnaire reached a sensitivity/specificity of 0.82/0.81 in 3-to 6-year-olds (Gao et al, 2010). However, additional risk factors (e.g., plaque, bacterial tests, salivary factors, exposure to fluoride) do not seem to markedly improve the prediction in older schoolchildren, adolescents, and adults (Disney et al, 1992;Vanobbergen et al, 2001; Stenlund et al, 2002;Twetman and Fontana, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…32,95,113,120,121 On a population basis, CRA can identify groups of children at high risk and action can be taken to optimize resource allocation in a public health system to prevent and treat caries. 108,122,123 Several CRA tools have been developed recently which include simple dietary assessment. These include the Pediatric Risk Assessment Tool (PRAT), 10 the CAT 104 and a community screening model with a sensitivity ⁄ specificity of 82% ⁄ 73%.…”
Section: Sweet Drinks and General Health Of Childrenmentioning
confidence: 99%
“…These include the Pediatric Risk Assessment Tool (PRAT), 10 the CAT 104 and a community screening model with a sensitivity ⁄ specificity of 82% ⁄ 73%. 123 Responding to increased soft drink intakes and decreased dairy product intakes in the US, the PRAT was developed at the University of Iowa in 2003. 10 A parent questionnaire addresses recalled fluid intake over the past 24 hours, recording total intake, frequency and timing of intake, focusing particularly on evening ⁄ night-time consumption.…”
Section: Sweet Drinks and General Health Of Childrenmentioning
confidence: 99%
“…Data were collected systematically considering demographic (Gender and Age), socioeconomic (Household Income and Paternal Education), dietary habits (Frequency and Type of Diet), hygiene habits (Frequency of Toothbrushing, Sulcus Bleeding Index -SBI and Simplified Oral Hygiene Index -OHI-S) -Box 1. Oral examinations were performed to estimate the dental caries experience on primary (dmft) and permanent (DMFT) according to WHO guidelines [8].…”
Section: Methodsmentioning
confidence: 99%
“…In this framework, understanding the distribution of caries is necessary to improve dental services and planning oral health strategies [7,8]. Therefore, epidemiological studies have evaluated the factors influencing the dental caries prevalence in children [9,10,11].…”
Section: Introductionmentioning
confidence: 99%